Examining Influential Factors of Students' Academic Burnout: A Case Study at a University in Yunnan, China - He, Chuanchuan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study explores the significance of influences among four independent variables—self-efficacy, self-compassion, professional identity, and life satisfaction—on the dependent variable, academic burnout. Research design, data and methodology: The research employed the Index of Item-Objective Congruence (IOC) to assess validity and Cronbach’s Alpha in a pilot test (n=30) to measure reliability. A total of 140 valid responses from students at Yunnan Minzu University were analyzed using multiple linear regression to verify significant relationships between variables. Following this, a group of 30 students participated in a 14-week Intervention Design Implementation (IDI). Afterwards, the quantitative results from post-IDI and pre-IDI assessments were analyzed using a paired-sample t-test for comparison. Results: The multiple linear regression analysis indicates that self-efficacy, self-compassion, professional identity, and life satisfaction significantly impact students' academic burnout. Additionally, the paired-sample t-test results reveal significant differences in self-efficacy, self-compassion, professional identity, life satisfaction, and academic burnout between the pre-IDI and post-IDI stages. Conclusions: This study offers implications for reducing academic burnout through the enhancement of self-efficacy, self-compassion, professional identity, and life satisfaction. The findings provide a foundation for designing targeted interventions and support programs in higher education aimed at promoting student well-being, academic engagement, and long-term personal and professional development.